Decent work in fisheries: Current trends and key considerations for future research and policy. (February 2022) - Garcia Lozano, Alejandro J.; Decker Sparks, Jessica L.; Durgana, Davina P.; Farthing, Courtney M.; Fitzpatrick, Juno; Krough-Poulsen, Birgitte; McDonald, Gavin; McDonald, Sara; Ota, Yoshitaka; Sarto, Nicole; Cisneros-Montemayor, Andrés M.; Lout, Gabrielle; et al.
Abstract: Labor issues and human rights violations have become the subject of rising concern in fisheries and seafood production. This paper reviews recent research on labor issues in the fishing industry, especially by environmental researchers and nongovernmental organizations (NGOs) which are emerging as key players in research and policy arenas. Recent research has focused largely on severe violations such as forced labor, particularly in 'hotspot' geographies, often relying on indicators and risk-based approaches given the paucity of data and challenges of monitoring working conditions. This paper proposes that decent work – a concept associated with the institutional history of the International Labor Organization (ILO) but with broad implications – can contribute to overcoming gaps in the research landscape, and assessing and improving a range of labor issues in fisheries. The paper elaborates some key considerations for studying and promoting decent work in the seafood industry. Assessing and achieving decent work in the world's fisheries requires (1) a holistic human rights approach to decent work, in which labor concerns are understood in the context of interrelated and interdependent sets of human rights, (2) consideration of the complex political-economic regimes and histories in which seafood production is embedded, and perhaps most importantly, (3) that workers play a central role and have a voice in defining and achieving decent work. The paper concludes with future directions for research and a discussion of promising and emerging policy pathways for promoting decent work in fisheries and seafood production. Highlights: Attention is growing on labor issues in fisheries and seafood production. Recent research focuses largely on severe abuses in hotspot geographies. Focus is also on harvest stage of production and using indicators and risk-analysis. Decent work is a holistic, comprehensive concept that can guide future work. Multiple governance and policy pathways for promoting decent work are examined.